HUBUNGAN ANTARA KEBUGARAN JASMANI DENGAN MOBILITAS GERAK PADA ATLET FUTSAL KOTA BANDUNG - Alvino Ferdinand Rahman, - (2022)
Mobility refers to the human activity of moving from one place to another, generally by walking or running. Physical fitness is the ability of a person's body to carry out daily tasks and work without causing significant fatigue so that the body still has energy reserves to cope with the load. Extra work. This study aims to determine the relationship between physical fitness and mobility in futsal skills. The method used in this study uses a quantitative descriptive method with a correlational design. The sampling technique in this study used a purposive sampling technique. The sample in this study was 5 athletes who were members of the Bandung City Porprov team. The instruments used were the Beep Test, Illinois Agility Test, Dash Sprint Test 20 meter and Mobility test using the Kinovea Software. The results of calculating the Pearson product-moment correlation test and multiple regression using IBM SPSS Statistics 23. The results obtained from the research. 0.015 <0.05, it can be concluded that there is a correlation between fitness and motion mobility. The calculated r value shows a positive result indicating that the correlation between the two variables is positive, which means that the more fitness increases, the better the mobility of the futsal athletes.